$2N+1$-Soliton Solutions of Boussinesq-Burgers Equation (Communications in Mathematical Research, 2020)
$2N+1$-soliton solutions of Boussinesq-Burgers equation are obtained by using the Hirota bilinear derivative method and the perturbation technique. Further, we give the graphs of corresponding three- and five-soliton solutions.
Keywords: Boussinesq-Burgers equation; Hirota bilinear derivative method; $2N+1$-soliton solution